How did the Global Financial Crisis Influence the Automobile Industry: Comparison between the US and Japanese Auto Industry - SUN, YAN (2013)
The 2008 global financial crisis was the worst one in seventy-five years and had great negative impact on the economy worldwide. Automobile industry, the pillar to the economic development, was hit most by the recession among the sectors. The purpose of this study is to analyze the financial crisis impacts on the automobile industry and find out strategies to decrease the occurrence rate and the loss if a similar crisis occurs.